Development of HfO₂-Based Solar-Blind SAW UV-C Sensor for Corona Discharge Detection Application - Lee, Hyunho; Nawaz, Faisal; Shim, Eeunsun; Lee, Jinjae; Choi, Cheol; Lee, Keekeun (Applied Sciences (Switzerland), 2025)
This study presents a novel surface acoustic wave (SAW)-based solar-blind ultraviolet-C (UV-C) corona sensor, marking the first reported use of HfO₂ as a sensing material for UV-C corona sensing. A 222 MHz two-port SAW delay line structure was selected as a sensor platform, and its optimal parameters were determined through Coupling of Mode (COM) modeling analysis. COMSOL simulations were conducted to investigate the effect of UV-C exposure on the HfO2 thin film, highlighting its contribution to conductivity changes. A 30 nm-thick HfO2 thin film was deposited using atomic layer deposition (ALD) within the cavity of a two-port SAW delay line, providing sufficient volume and density of absorption sites for UV-C exposure. Comprehensive material characterization of the HfO2 thin film was performed using X-ray diffraction (XRD), scanning electron microscopy (SEM), and energy-dispersive X-ray spectroscopy (EDS). The effect of annealing temperature was analyzed in detail, with results confirming that 500 °C is the optimal temperature for achieving the best performance in a SAW-based UV-C corona sensor. The sensor characteristics were measured using custom-made interface electronics, allowing frequency shifts to be visually observed on a PC monitor with compensation for environmental factors such as humidity and temperature. The developed sensor demonstrated response and recovery times of 2.8 s and 4 s, respectively, with a measured sensitivity of 563 ppm/(mW·cm−2). Furthermore, the effect of HfO₂ film thickness on the sensor’s response to UV-C exposure was examined in detail, showing that increased thickness leads to a higher frequency shift, thereby enhancing sensitivity. The feasibility of the sensor for real-world applications was validated through successful testing under simulated corona discharge detection.
Keywords: Corona; Corona discharges; Frequency shift; HfO 2; HfO2 sensing material; Sensing material; Solar blind; Surface acoustic waves; Thin-films; Ultraviolet-C; corona; frequency shift; HfO2 sensing material; oscillator; sensor; surface acoustic wave; UV-C